Copper and Lithium Industrialization by Major Producing Countries for Mining Sustainability - Coayla, Edelina; Romero, Violeta (International Journal of Energy Economics and Policy, 2024)
This research objective is to analyze the prospects of copper and lithium industrialization for the mining sustainability of the world’s major producing countries. An expo-facto design was used based on a documentary analysis, considering the world ranking of the top copper-producing countries, where Chile, Peru, China, and the Democratic Republic of Congo stand out, and regarding lithium production, Australia, Chile, China, and Argentina stand out. On a global level, the presence of South American countries with mining resources in exploration and extraction is relevant; in contrast, China, a mining country, not only extracts natural resources but has advanced in the value chain with competitive advantages and consequent economic development; for its part, the DR of Congo (Africa), has ascended in the copper extraction ranking. The motors and electrical systems of electromobility vehicles are manufactured with copper and the batteries with lithium, which contributes to the mitigation of greenhouse gas emissions and thereby to environmental sustainability. Furthermore, the correlation between copper and lithium demand for electric vehicles in a 2050 zero-emission scenario is strong. There are social conflicts, mainly over the use of water; therefore, it is necessary to implement mining policies that lead to sustainable development.